Text in the world of synergized codes - Warchala, Jacek (Papers in Linguistics, 2020)
This study deals with the problem of limits of philological research in the context of the evolution of philology towards anthropology of language and transgression (in the multimedia age) of limits of a traditionally understood text. Its main subject is advertising communication conceived as multicodal and multimodal text in which meaning results from the interference of particular semiotic systems (codes): verbal, iconic (visual), musical or, in some instances, the code of arranged space. The study considers the issue of mutual dependence of the verbal and iconic codes (or word and image) within a single advertising text. Three types of dependence are pointed out: metaphorical, metonymical and tautological.